Clinical Outcomes by Race and Ethnicity in the Systolic Blood Pressure Intervention Trial (SPRINT): A Randomized Clinical Trial. (23rd August 2017) - Still, Carolyn H; Rodriguez, Carlos J; Wright, Jackson T; Craven, Timothy E; Bress, Adam P; Chertow, Glenn M; Whelton, Paul K; Whittle, Jeffrey C; Freedman, Barry I; Johnson, Karen C; Foy, Capri G; He, Jiang; et al.
Abstract: BACKGROUND: The Systolic Blood Pressure Intervention Trial (SPRINT) showed that targeting a systolic blood pressure (SBP) of ≤ 120 mm Hg (intensive treatment) reduced cardiovascular disease (CVD) events compared to SBP of ≤ 140 mm Hg (standard treatment); however, it is unclear if this effect is similar in all racial/ethnic groups. METHODS: We analyzed SPRINT data within non-Hispanic White (NHW), non-Hispanic Black (NHB), and Hispanic subgroups to address this question. High-risk nondiabetic hypertensive patients ( N = 9, 361; 30% NHB; 11% Hispanic) 50 years and older were randomly assigned to intensive or standard treatment. Primary outcome was a composite of the first occurrence of a myocardial infarction, acute coronary syndrome, stroke, decompensated heart failure, or CVD death. RESULTS: Average postbaseline SBP was similar among NHW, NHB, and Hispanics in both treatment arms. Hazard ratios (HRs) (95% confidence interval) (intensive vs. standard treatment groups) for primary outcome were 0.70 (0.57–0.86), 0.71 (0.51–0.98), 0.62 (0.33–1.15) (interaction P value = 0.85) in NHW, NHB, and Hispanics. CVD mortality HRs were 0.49 (0.29–0.81), 0.77 (0.37–1.57), and 0.17 (0.01–1.08). All-cause mortality HRs were 0.61 (0.47–0.80), 0.92 (0.63–1.35), and 1.58 (0.73–3.62), respectively. A test for differences among racial/ethnic groups in the effect of treatment assignment on all-cause mortality was not significant (Hommel-adjusted P value = 0.062) after adjustment for multiple comparisons. CONCLUSION: Targeting a SBP goal of ≤ 120 mm Hg compared to ≤ 140 mm Hg led to similar SBP control and was associated with similar benefits and risks among all racial ethnic groups, though NHBs required an average of ~0.3 more medications. CLINICAL TRIALS REGISTRATION: Trial Number NCT01206062, ClinicalTrials.gov Identifier at https://clinicaltrials.gov/ct2/show/NCT01206062 .